Timing of induction of labour in the prevention of prolonged pregnancy: Systematic review with meta‐analysis. Issue 1 (20th June 2022) - Geneen, Louise J.; Gilbert, James; Reeves, Tim; Mainie, Pramod; Maresh, Michael; Smith, Lisa; Wu, Pensee; Parisaei, Maryam
Abstract: Objective: To update the systematic review which informed the National Institute for Health and Care Excellence guideline "Inducing Labour" (NG207), including additional data and analyses, and comparison with a recent individual patient data analysis of 41‐ versus 42‐week induction. Search Strategy: Multiple database search (including Cochrane Central Register of Controlled Trials, MEDLINE, and Embase) from inception to 10th September 2021 for randomised controlled trials (RCTs) comparing different induction timing in uncomplicated singleton pregnancies. Data Collection and Analysis: One reviewer screened, extracted, analysed, and assessed the quality/certainty of the evidence (using ROB1 and GRADE), with second reviewer verification. Main Results: Five week‐to‐week comparisons, and one overall comparison (induction vs. delayed induction, 20 RCTs, n  = 15 725 pregnant women) for assessment of predefined subgroups. Most data were for 41 versus 42 weeks and 39 versus 41 weeks: 10 times as many participants as the other week‐to‐week comparisons. There was evidence of an effect at 41 versus 42 weeks (five RCTs, n  = 5819) in favour of 41‐week induction: fewer perinatal deaths and neonatal intensive care unit admissions (low‐to‐moderate certainty of the evidence); there was no evidence of an effect in either direction for the remaining outcomes (very‐low to moderate certainty). There was no evidence of an effect for outcomes reported for: 40 versus 42 weeks (three RCTs, n  = 668, very‐low to low certainty); 39 versus 42 weeks (three RCTs, n  = 1103, very‐low to moderate certainty); 39 versus 41 weeks (four RCTs, n  = 7101, very‐low to low certainty); and 41/42 versus 43/44 weeks (four RCTs, n  = 954, very‐low to low certainty). Conclusion: The evidence supports offering induction at 41 + 0 weeks compared to 42 + 0 weeks to reduce adverse perinatal and obstetric outcomes. Practioners points: 1. Evidence supports offering induction at 41 + 0 weeks compared to 42 + 0 weeks to reduce adverse perinatal outcomes in uncomplicated singleton pregnancies. 2. Other week‐to‐week comparisons require more data for all outcomes. 3. More data is needed for all week‐to‐week comparisons for women at potentially higher risk for adverse outcomes: black, Asian, and minority ethnic groups, higher body mass index (30+), older (35+ years), and women who conceived using artificial reproductive technology.